2017
DOI: 10.1002/pd.5158
|View full text |Cite
|
Sign up to set email alerts
|

Advanced genomic testing may aid in counseling of isolated agenesis of the corpus callosum on prenatal ultrasound

Abstract: In accordance with current guidelines, we conclude that microarray should be offered in case of isolated cACC on ultrasound. ES is likely to be informative for prenatal counseling and should be offered if microarray is normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…A recent study showed that, in fetuses with normal microarray results, exome sequencing will detect additional defects in up to 13%, and this may become the new standard of care in the near future. 23 Additionally, the routine use of MRI in fetuses with agenesis of the corpus callosum is appropriate, given the high incidence of cortical anomalies in this group. The relatively low rate of MRI and genetic testing in our cohort (≈50%) is mainly explained by the fact that it was not performed in cases in which the results would not have changed the decision of the parents regarding further pregnancy management (termination versus continuation of the pregnancy).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that, in fetuses with normal microarray results, exome sequencing will detect additional defects in up to 13%, and this may become the new standard of care in the near future. 23 Additionally, the routine use of MRI in fetuses with agenesis of the corpus callosum is appropriate, given the high incidence of cortical anomalies in this group. The relatively low rate of MRI and genetic testing in our cohort (≈50%) is mainly explained by the fact that it was not performed in cases in which the results would not have changed the decision of the parents regarding further pregnancy management (termination versus continuation of the pregnancy).…”
Section: Discussionmentioning
confidence: 99%
“…More specific to agenesis of the corpus callosum, a retrospective study of 16 cases of prenatally identified agenesis of the corpus callosum showed four individuals underwent whole-exome sequencing and two had positive results, yielding a diagnostic rate of 12.5%-50%. 17 Importantly, after postnatal evaluation many of the individuals in this cohort were shown to have other anomalies in addition to agenesis of the corpus callosum. Larger prospective studies are needed to evaluate the utility of whole-exome sequencing in cases of true isolated agenesis of the corpus callosum.…”
Section: Discussionmentioning
confidence: 89%
“…The validity of our study is nevertheless limited by the quality of the original studies, all of which had a retrospective design, a small sample size and were heterogeneous in gestational age at ultrasound and MRI assessment. The interval between ultrasound and MRI was not specified [25][26][27][28][29][30][31][32]35 or varied markedly across studies, ranging from 14 days 8,33,35,36 to more than 4 weeks. 24 Therefore the role of MRI might have been overestimated due to the evolutive nature of some abnormalities (such as heterotopias) rather than the imaging method used for detecting them.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 540 were identified; 109 were assessed with respect to their eligibility for inclusion and 14 studies were included in the systematic review (Tables 1 and S1, Figure 1). 8,[24][25][26][27][28][29][30][31][32][33][34][35][36] The results of the quality assessment of the included studies are presented in Table 2. Most of the included studies showed a good overall score.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation